Metabolomics and Transcriptomics Integration of Early Response of Populus tomentosa to Reduced Nitrogen Availability - Chen, Min; Yin, Yiyi; Zhang, Lichun; Yang, Xiaoqian; Fu, Tiantian; Huo, Xiaowei; Wang, Yanwei (Frontiers in Plant Science, 2021)
Nitrogen (N) is one of the most crucial elements for plant growth and development. However, little is known about the metabolic regulation of trees under conditions of N deficiency. In this investigation, GC-MS was used to determine global changes in metabolites and regulatory pathways in Populus tomentosa. Thirty metabolites were found to be changed significantly under conditions of low-N stress. N deficiency resulted in increased levels of carbohydrates and decreases in amino acids and some alcohols, as well as some secondary metabolites. Furthermore, RNA-Seq analysis was performed to characterize the transcriptomic profiles, and 1,662 differentially expressed genes were identified in P. tomentosa. Intriguingly, four pathways related to carbohydrate metabolism were enriched. Genes involved in gibberellic acid and indole-3-acetic acid pathways were found to be responsive to low-N stress, and the contents of hormones were then validated by HPLC-ESI-MS/MS. Coordinated metabolomics and transcriptomics analysis revealed a pattern of co-expression of five pairs of metabolites and unigenes. Overall, our investigation showed that metabolism directly related to N deficiency was depressed, while some components of energy metabolism were increased. These observations provided insights into the metabolic and molecular mechanisms underlying the interactions of N and carbon in poplar.